Relationship between the attitudes of biology education students towards statistics with knowledge of data analysis - Ahmad Fauzi; Diani Fatmawati; Ali Usman Hali (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Students' knowledge of data analysis determines the quality of the research they report but they tend to perceive courses on statistics or data analysis as challenging and unappealing. The present study aimed to investigate the correlation between biology education students' attitudes toward statistics and their proficiency in determining various data analytical techniques. This study involved biology education students from the Universitas Muhammadiyah Malang who had completed a course in statistics, research methods, and data analysis. The Survey of Attitudes Toward Statistics (SATS) and the Statistics Assessment of Graduate Students (SAGS) were used sequentially as instruments for collecting data on student attitudes toward statistics and data analysis competencies. The results revealed that while most students had positive attitudes toward statistics, they perceived the subject as challenging to learn. Additionally, the students demonstrated low levels of competency in data analysis. The aspects of cognitive competence and difficulty from SATS correlate significantly with their SAGS score. These results suggest that there is a need for a revision of the biology education curriculum to better equip students with the skills and knowledge to increase their data analysis competencies.